Оценка влияния зернистости абразива на шероховатость поверхности при абразивной обработке - Шкурупий, Валентин Григорьевич; Новиков, Федор Васильевич; Крюк, Анатолий Григорьевич (Национальный технический университет "Харьковский политехнический институт", 2014)
В работе с позиции теории вероятностей получены аналитические зависимости для определения параметров шероховатости поверхности при абразивной обработке, рассматривая режущие зерна в форме сферы. Произведена оценка влияния зернистости абразивных зерен на шероховатость поверхности. Теоретически установлено, что с уменьшением зернистости абразивного порошка параметры шероховатости поверхности уменьшаются фактически по линейной зависимости. Это указывает на возможность фактически неограниченного уменьшения шероховатости поверхности с уменьшением зернистости абразивного порошка. Установлено также существенное влияние скорости радиальной подачи на шероховатость поверхности

In dealing with the position of the probability theory, analytical dependence for the determination of surface roughness when sanding considering cutting grain in the form of a sphere. An assessment of the impact of grit abrasive grains on the surface roughness. Theoretically found that with decreasing grain size of the abrasive powder surface roughness decreases virtually linearly. This indicates the possibility of virtually unlimited reduce surface roughness with decreasing grain size of the abrasive powder. It has also a significant impact velocity radial flow on the surface roughness, it decreases with decreasing velocity of radial flow. In the simulation of the abrasive grains in the form of spheres surface roughness takes smaller values as compared with the case where the abrasive grain pattern-ruyutsya in the form of a cone. This brings the calculated data to the practical data. Develop practical recommendations for improving the processing of loose abrasive surfaces of machine parts, based on the developed mathematical model formulated the basic conditions reduce the roughness of machined surfaces when sanding
Assessing the impact of grit abrasive surface roughness when sanding
Keywords: режущие зерна; параметры; абразивный порошок; скорость радиальной подачи; abrasion; grai; surface roughness; loose